RANCANG BANGUN DUAL AXIS SOLAR TRACKER MENGGUNAKAN LENSA FRESNEL BERBASIS INTERNET OF THINGS (IOT) UNTUK OPTIMASI DAYA OUTPUT SOLAR CELL - Kurniawansyah, Rifki Mohamad; Kusmita, Aryu; Ayu, Humairoh Ratu (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
A single-axis solar tracker using a Fresnel lens has been realized to optimize the output power of solar cells. The solar tracker system is monitored using a website that displays the value of voltage (volts), current (amperes), tilt angle (0), and output power (watt) in real-time. This single-axis solar tracker is designed using a 20 Wp solar panel, Fresnel lens, Solar Charger Controller, Accumulator, Arduino Nano, ESP32, Buck Converter, L298N motor driver, FZ0430 sensor as voltage meter, ACS712 sensor as current meter, MPU6050 sensor as angle meter. The method used in this research includes collecting data on voltage, current, tilt angle, power generated by solar panels, and light intensity and temperature emitted by the sun for 3 days without and 3 days using lenses. This tool can measure the voltage value of direct electricity with an error rate of 1.88%, accuracy of 98.12%, and precision of 99.15%. The electric current measurement has an error rate of 3.82%, an accuracy of 96.18%, and a precision of 96.84%. Light measurement has an error rate of 1.85%, an accuracy of 98.15%, and a precision of 98.78%. The angle measurement has an error rate of 5.95% and an accuracy of 94.05%. The single-axis solar tracker system using Fresnel lenses has a power efficiency of 37.09% compared to the single-axis solar tracker without Fresnel lenses.